Mechanical-magneto coupled model of polymer-bonded magnetostrictive composites - Ran Zhao; Bowen Wang; Yafang Li; Shuying Cao; Jianwu Yan (Functional Materials, 2016)
In order to accurately predict the magneto-elastic property of polymer-bonded magnetostrictive materials, a new mechanical-magneto coupled nonlinear model is proposed in this paper. In the proposed model, the total strain of the composites is expressed by the matrix strain, magnetostriction eyestrains and strain concentration factors. Firstly, the interaction between the matrix and inclusion phase of the magnetostrictive composites is analyzed and the strain concentration factors are calculated with the Mori-Tanaka mean field method. Then, the magnetization process of the composites is analyzed in detail according to the demagnetizing field theory. Finally, the proposed model of magnetostrictive composites is obtained. Furthermore, in order to verify the proposed model, the performance of the magnetostrictive composites is tested, and the theoretical calculations are also compared with the experimental data. The results show that the given model can greatly simulate the stress concentration and precisely predict the magnetostrictive coefficient, saturation magnetostrictive coefficient as well as the magnetization of the composites.